Potential effects of Asian-adapted Mediterranean diet in depression and anxiety among women with metabolic dysfunction-associated steatotic liver disease: a secondary analysis - Salamanca-Sanabria, Alicia; Chooi, Yu Chung; Loo, Evelyn Xiu Ling; Lai, Xianning; Volchanskaya, Vera Sergeyevna Brok; Chong, Yap Seng; Eriksson, Johan Gunnar (Frontiers in Nutrition, 2025)
BackgroundCommon Mental Disorders (CMDs) such as anxiety and depression have been associated with metabolic dysfunction–Associated steatotic Liver Disease (MASLD). The Mediterranean Diet (MD) has been shown to improve metabolic health and reduce CMDs. We previously reported that a calorie-restricted MD adapted to the Asian food culture has beneficial effects on body composition, liver fat, and cardiometabolic markers in Chinese Singaporean women with MASLD.ObjectiveThis secondary analysis examines the effects of an Asian-adapted MD on the symptoms of anxiety and depression in the same population.MethodsIn a double-blind, parallel-design, randomized controlled trial, 84 Chinese- Singaporean females with MASLD were randomly assigned to 1 of the 3 groups for 12 weeks: adapted Asian MD with C15:0 supplementation (n = 29), diet without C15:0 supplementation (n = 26), or control (habitual diet and no C15:0 supplementation, n = 29). Depression and anxiety symptoms were assessed using the Beck Inventory Questionnaire (BDI-II) and the State–Trait Anxiety Inventory (STAI).ResultsPaired t-tests showed a statistically significant reduction in anxiety and depression symptoms within the groups. Particularly, the Diet+C15 group showed a significant decrease in trait anxiety scores (M = 38.62, SE = 1.84 to M = 34.10, SE = 1.73), t (28) = 3.73, p < 0.001, with a medium-to-large effect size (d = 0.69) Jacobson and Truax’s reliable change criteria showed clinically reliable improvements in anxiety and depression postintervention.ConclusionThe Asian-adapted MD shows potential benefits for reducing anxiety and depression symptoms, particularly trait anxiety in women with MASLD. However, given the complexity of CMD, findings should be interpreted cautiously. Future research with larger sample sizes is needed to confirm these effects and explore underlying mechanisms.Clinical trial registrationhttp://clinicaltrials.gov, NCT05259475.